(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2025)
ABSTRACT Literature serves as a mechanism for reinforcing an author’s ideology. Ideology, in this context, refers to a set of values, principles and beliefs that form the foundation of an individual’s, society’s, nation’s or state’s worldview. Faisal Tehrani’s novel Bila Tuhan Berbicara (2007) embodies principles and values that not only influence its narrative but also shape the framework of his beliefs and thoughts.While many previous studies have discussed the relationship between ideology and literature, there is a lack of detailed research on the ideology of an author derived from specific Quranic surahs, such as the conceptual thought of Ashabul Kahfi and its profound manifestation within the narrative of a literary work. This gap highlights a significant shortcoming in modern literary discourse, particularly in the context of Faisal Tehrani’s writings.Using a qualitative approach based on textual analysis, this study aims to analyse how the ideological concept of Ashabul Kahfi is manifested by Faisal Tehrani in his novel Bila Tuhan Berbicara. The discussion focuses on the process and relationship of Ashabul Kahfi’s ideology in shaping a set of values, principles, and beliefs within the world of Bila Tuhan Berbicara. The findings reveal that three types of Ashabul Kahfi thought serve as the main driving forces of the narrative in the novel. This study offers a significant contribution to expanding modern literary discourse, especially in works that creatively incorporate religious and philosophical themes. ABSTRAK Kesusasteraan berfungsi sebagai mekanisme pengukuhan ideologi pengarang. Ideologi, dalam konteks ini merujuk kepada satu set nilai, prinsip dan kepercayaan yang menjadi asas kepada pandangan hidup individu, masyarakat, bangsa atau negara. Justeru novel Bila Tuhan Berbicara (2007) karya Faizal Tehrani merangkumi prinsip dan nilai yang bukan sahaja mempengaruhi naratif tetapi juga membentuk kerangka kepercayaan dan pemikiran beliau. Walaupun banyak kajian terdahulu telah membincangkan hubungan antara ideologi dan kesusasteraan, terdapat kekurangan kajian tentang ideologi pengarang yang diangkat dari salah satu surah Al Quran, seperti konsep pemikiran Ashabul Kahfi dan dimanifestasikan konsep ideologi ini secara mendalam dalam naratif sesebuah karya. Kekurangan ini bertindak sebagai jurang yang signifikan dalam wacana kesusasteraan moden terutama dalam konteks karya Faisal Tehrani.Melalui pendekatan kualitatif yang berasaskan kepada analisis tekstual, kajian ini bertujuan untuk menganalisis bagaimana konsep ideologi Ashabul Kahfi dimanifestasikan oleh Faizal Tehrani dalam novel Bila Tuhan Berbicara. Fokus perbincangan adalah tertumpu kepada proses dan hubungan ideologi Ashabul Kahfi dalam pembentukkan sebuah set nilai, prinsip dan kepercayaan dunia Bila Tuhan Berbicara. Dari hasil kajian mendapati tiga jenis pemikiran Ashabul Kahfi menjadi penggerak utama naratif dalam novel tersebut. Kajian ini berfungsi sebagai sumbangan penting dalam memperluaskan wacana ideologi sastera moden, terutama dalam konteks karya yang mengangkat tema keagamaan dan falsafah secara kreatif.